Validation of control diets for lactose and fish meal replacement studies in nursery pigs - Sulabo, R.C.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The objective of this study was to develop and validate control test diets to be used for lactose and fish meal replacement studies in nursery pigs. A total of 180 nursery pigs (PIC, initially 16.6 lb and 28 ± 2 d of age) were blocked by initial weight and randomly allotted to 1 of the following 6 dietary treatments: (1) negative control (NC) diet based on corn-soybean meal, (2) NC + 10% food-grade whey, (3) NC + 10% feed-grade whey, (4) Diet 2 + 4.5% select menhaden fish meal, (5) Diet 2 + 2.25% select menhaden fish meal and 1.25% spray-dried blood cells, and (6) Diet 2 + synthetic amino acids. Diets 4 to 6 also contained 10% food-grade whey. Each treatment had 5 pigs per pen and 6 replications (pens). Diets were formulated to contain 1.37% standardized ileal digestible lysine and 1,495 kcal ME/lb and were fed in meal form. Newly-weaned pigs (21 ± 2 d of age) were fed a common segregated early weaning and transition diet for 7 days then fed the experimental phase 2 diets for 21 d. From d 0 to 7 and 0 to 14, pigs fed the diet containing 10% feed-grade whey tended to have greater ADG (P < 0.07) and heavier (P < 0.08) BW than pigs fed the negative control diet, with pigs fed the diet containing 10% food-grade whey being intermediate. Pigs fed the negative control diet with either added food- or feed-grade whey tended to have better (P < 0.06) F/G than pigs fed the phase 2 diet solely based on corn and soybean meal. Pigs fed phase 2 diets containing either 4.5% select menhaden fish meal or the combination of 2.25% select menhaden fish meal and 1.25% spray-dried blood cells tended to have greater ADG (P < 0.07) and BW (P < 0.07) than pigs fed the diet containing 10% food-grade whey. Pigs fed the diet with increased synthetic amino acids had similar (P > 0.36) ADG and BW compared with pigs fed the diet containing the same food-grade whey without specialty proteins but tended to have poorer (P < 0.09) F/G than pigs fed the diet containing food-grade whey during d 0 to 7. Overall (d 0 to 21), only numerical differences (P > 0.15) were observed in ADG, ADFI, F/G, and pig BW among the dietary treatments. More research is needed to evaluate the use of synthetic amino acids as a replacement for high quality protein ingredients in nursery diets. When reviewing data from previous studies, it is apparent that further development of the control diets for testing lactose and fish meal sources is needed so that the predicted response is consistent.
Keywords: Lactose; Protein sources; Synthetic amino acids; Weanling pigs; Swine